ANALISA DAN KAJIAN EKSPERIMENTAL PENGARUH PENAMBAHAN SERAT BENDRAT (SERAT KAWAT) PADA DAERAH TARIK BALOK BETON BERTULANG - Mariance Napitupulu (Jurnal Teknik Sipil USU, 2014)
ABSTRACT Rebars is the most expensive material in the construction. Bendrat fiber / wire fiber was selected material because aside from having the material factors - factors principles concrete reinforcing, but also easily obtained. This experiment was done with cylinders (15x30) and reinforced concrete beams (15x25x320 with addition of 2% bendrat/wire fiber in the tensile’s area of reinforced concrete beam. The result of this experiment showed that compressive strength of concrete increase 37.22% when using bendrat / wire fiber. However, a significant increase occurred in tensile strength, that was 74.52%. The test were done to reinforced concrete beams showed decreasing of deflection 35.26% and Increasing flexural capacity 27.97%. Coefficient of comparison between of load test (P) and load theory (Pn) of reinforced concrete beams without bendrat / wire fiber (normal )is 0.9903 and with bendrat / wire fiber is 0.7335. Coefficient of comparison between collapse load testing (P) and the analytical ultimate load (Pu) of reinforced concrete beams without bendrat / wire fiber: coefficient (φ) = 1.6 and with bendrat / wire fiber: coefficient (φ) = 1.15. Keyword: Bendrat Fiber, Wire Fiber, Reinforced Concrete Beams